Construction of a modified live HP-PRRS virus vaccine and an attenuated listeria vaccine vector using reverse genetics - Ren, Jie (Kansas State University, 2014)
The development of reverse genetics systems for the manipulation of viral and bacterial genomes has provided platforms for identifying virulence genes, studying pathogenesis and developing vaccines. Replication-competent vaccines (e.g., modified live virus (MLV) vaccines and replicating viral/bacterial vectors) are considered the most efficacious approach for vaccine development. We constructed replication-competent candidate vaccines for two viral diseases in pigs via reverse genetics. The first vaccine we designed is to protect against highly pathogenic porcine reproductive and respiratory syndrome virus (HP-PRRSV). HP-PRRSV can cause high mortality in pigs of all ages. Vaccines to protect pigs from HP-PRRSV are not commercially available in the US. According to previous studies, the non-structural protein (NSP) coding region of HP-PRRSV is closely related to the high mortality rate and the structural protein (SP) coding region contributes to the induction of broadly protective neutralizing antibodies. We created a chimeric PRRSV, of which the SP coding region was derived from HP-PRRSV and NSP coding region was derived from a low-pathogenic strain. This chimeric PRRSV caused similar CPE in cells as parental viruses, but had slower growth kinetics. We hypothesize that this chimeric virus will have a low pathogenicity and could serve as a candidate vaccine that can provide protection against HP-PRRV. The second vaccine vector is a modified Listeria innocua (L.inn), a non-pathogenic strain of Listeria. Genetically related Listeria monocytogenes (L.m) is a well-known intracellular pathogen that encodes specialized virulent determinants facilitating its intracellular growth and spread. Our goal is to make L.inn a vaccine vector that can deliver classical swine fever (CSF) viral antigen into intracellular environments by complementation of L.inn with selected L.m virulence genes necessary for intracellular survival and induction of a robust immune response. In this study, we constructed a shuttle vector pHT-E2 that can express CSFV antigen E2 in L.inn. We cloned the plcA-prfA operon of L.m virulence gene cluster (vgc) into pHT-E2, which enhanced the expression of E2 in L.inn. In future studies, we plan to clone additional L.m virulence genes into the shuttle vector to increase immunogenicity of this recombinant L.inn and test its ability to protect pigs from CSFV.
Keywords: PRRSV; MLV vaccine vector; Listeria; Veterinary Medicine (0778)